Successful conversion surgery for locally advanced gallbladder cancer after gemcitabine and nab-paclitaxel chemotherapy - Ziyi Yang; Ziyi Yang; Ziyou Wu; Ziyou Wu; Yichen Xiong; Yichen Xiong; Shilei Liu; Shilei Liu; Chen Cai; Chen Cai; Ziyu Shao; Ziyu Shao; et al. (Frontiers in Oncology, 2022)
ObjectiveGallbladder cancer (GBC) is highly malignant and is often diagnosed at the advanced stage. Lack of opportunity to surgery results in an unsatisfactory outcome. This pilot study employed gemcitabine combined with nab-paclitaxel (AG) as a conversion therapeutic measure for locally advanced GBC and successfully achieved conversion surgery in three initially unresectable GBC patients. We will introduce our experience on improving the outcome of this dismal disease.MethodsRadiology and nuclear medicine imaging were performed in each patient, and resectability was evaluated by joint consultation of our multi-disciplinary team (MDT). Patients evaluated as unresectable were treated with the AG regimen and re-evaluated for treatment response. When complete or partial response is achieved, MDT opinion would be required to assess the possibility of performing conversion surgery with R0 resection.ResultsThree GBC patients who were initially evaluated as unresectable successfully underwent R0 resection after conversion therapy with the AG regimen. The first case was a recurrent GBC patient evaluated as locally advanced and eventually achieved pathological complete response. The second case was a GBC patient who underwent R1 resection with residual lesions in the gallbladder bed and isolated No. 16 lymph node metastasis and who had a pathologically complete response after treatment. The third case had multiple but resectable liver metastases; both objective response and partial pathologic response were achieved. None of the patients experienced serious treatment-related adverse events. All cases revealed no evidence of recurrence or metastasis after a median follow-up of 12 months.ConclusionsConversion therapy shows a favorable efficacy in those unresectable GBC patients. Gemcitabine plus nab-paclitaxel has the potential to be used as a preoperative treatment option for GBC patients at the advanced stage. To further explore the efficacy of AG on conversion therapy for GBC patients, a prospective clinical trial has been registered (ChiCTR2200055698).